Intraoperative Pharmacotherapeutic Blood Management Strategies in Total Knee Arthroplasty - Banerjee, Samik; Issa, Kimona; Pivec, Robert; McElroy, Mark J.; Khanuja, Harpal S.; Harwin, Steven F.; Mont, Michael A. (The Journal of Knee Surgery, 2013)
Bone and soft tissue bleeding often results in substantial amounts of blood loss following total knee arthroplasty. Multiple studies have reported that cumulative blood loss varies between 500 and 1,500 mL in primary settings. Increased perioperative blood loss frequently requires allogeneic blood transfusions to improve the hematocrit and the hemoglobin levels. However, allogeneic transfusion is associated with risks of immunosuppression, transfusion reactions, graft versus host disease, and transmission of infections. To avoid these problems and reduce costs of transfusion, multiple intraoperative pharmacotherapeutic strategies have been developed. The various pharmacotherapeutic agents currently used are tranexamic acid, epsilon-aminocaproic acid, fibrin, thrombin, lavage with epinephrine, and norepinephrine. However, the relative efficacy and the cost-effectiveness of these techniques may vary. Thus, the purpose of this study was to provide a brief overview of the relative efficacy of various intraoperative pharmacological methods currently in use for decreasing blood loss following total knee arthroplasty and describe their potential complications associated with their use.
Keywords: blood; loss; prevention; pharmacotherapy; knee; arthroplasty